Determining optimum cutting ages including timber production and carbon sequestration benefits in Turkish Pine Plantations - Keleş, Sedat (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study presents the optimum cutting ages in Turkish pine (Pinus brutia Ten.) plantations including timber production and carbon sequestration values in Turkey. Four different growing spaces are considered. The study also evaluates the effects of different discount rates and carbon prices on the optimum cutting ages using net present value approach. The growth and yield curves, biomass equations and carbon conversion factors as well as forest plantation costs and timber assortments revenues for Turkish pine plantations are used to determine the optimum cutting ages. The results of the case study showed that the integration of carbon sequestration benefits into timber production increased the optimum cutting ages of Turkish pine plantations for each growing spaces in order to sequester more carbon. The optimum cutting ages decreased depending on the increase in discount rates. When carbon prices increased the optimum cutting ages also increased.